The Problem of Class Abstractionism. (March 2023) - McCarthy, Michael A.; Desan, Mathieu Hikaru
With renewed interest in Marxism, class is back on the intellectual agenda. But so too is the familiar charge of "class reductionism." This charge conflates two distinct claims regarding what we term the structural and political primacy of class. Structural primacy refers to the determinant role of class in social explanation, whereas political primacy refers to its centrality in radical politics. Crossing these distinct claims, we identify four possible positions on the primacy of class. Here, we focus on the two that affirm the structural primacy of class. What we call "class abstractionism, " which presumes to derive the political primacy of class from an account of its structural primacy, ultimately relies on an abstract conception of class that effectively presupposes its political primacy. In contrast, a more adequate account of structural primacy—what we call "class dynamism"—requires us to abandon the presupposition of class's necessary political primacy.